Tomographic and aberrometric assessment of first‐time diagnosed paediatric keratoconus based on age ranges: a multicentre study. Issue 6 (30th December 2020) - Rocha‐de‐Lossada, Carlos; Prieto‐Godoy, Mario; Sánchez‐González, José‐María; Romano, Vito; Borroni, Davide; Rachwani‐Anil, Rahul; Alba‐Linero, Carmen; Peraza‐Nieves, Jorge; Kaye, Stephen B.; Rodríguez‐Calvo‐de‐Mora, Marina
Abstract: Purpose: To describe paediatric keratoconus (KC) patients by tomographic and aberrometric characteristics at first diagnosis, in a multicentre study. Methods: We included 278 eyes from 139 paediatric patients, with a first tomographic diagnosis (Pentacam ® ) of KC prior to 18 years old. KC classification was based on the KC Index (≥ 1.07) and Topographic Keratoconus Classification (TKC ≥ 1). Patients were divided based on age ranges (14 and under and over 14 years) and gender. Statistical analysis was performed with SPSS statistics 25.0. ANOVA factor was carried out comparing to compare groups. Results: 278 eyes were screened, and 230 eyes were diagnosed with paediatric KC. Mean age was 15.48 ± 2.33 (6 to 18) years. We found differences in terms of TKC (2.08 ± 0.89 and 2.38 ± 0.82, p < 0.05) and spherical aberration (−0.71 ± 0.97 and −1.07 ± 1.36, p < 0.05) among the 14 years old or under and above 14 years old groups, respectively. Overall, female paediatric KC patients presented a more severe TKC, Belin Ambrosio Display, maximum keratometry, asphericity and primary and secondary coma aberrations compared to male KC patients. We observed a correlation between CDVA and asphericity (r = 0.71, p < 0.01), as well as between CDVA and spherical aberration (r = 0.69, p < 0.01). Conclusion: Our findings revealed that the debut of KC is usually in a moderate to advanced stage in the paediatric population at first diagnosis, particularly in female patients. Corneal tomography should be systematically performed in children with recent onset of corneal astigmatism.